Effect of processing and substitution levels of Ukwa (Treculia africana) on the anti-nutrient factors, in-vitro starch and protein digestibility and total essential amino-acid content of snack bars - Edima-Nyah, Anne P.; Ntukidem, Victor E.; Ekanem, Moses C.; Ojimelukwe, Philippa C.; Nwabueze, Titus U. (Frontiers in Sustainable Food Systems, 2023)
Introduction Ukwa (Treculia africana) is an indigenous edible seed. It is a strategic store of vital food nutrients that are available during a specific crucial time of the year when reliable sources of these nutrients are under cultivation and extremely scarce. In the past, only poor rural residents used to eat it, but today it is not only a specialty meal enjoyed by Nigeria's elite and metropolitan residents but also a source of foreign exchange. Methods In this study, Ukwa was processed into whole, dehulled, malted and defatted flours. Maize and coconut flours were blended with the respective Ukwa flours at the ratio of 0:95:5, 20:75:5, 25:70:5, 30:65:5, 35:60:5 and 95:0:5 for Ukwa flour:Maize flour:Coconut grits respectively for development of snack bars. A two-factor factorial experiment in a completely randomized block design was applied for the study of the effect of processing, substitution levels of Ukwa flour and the interaction of the two variables on the responses analyzed. Anti-nutrient content and proximate compositions of the flours were determined using standard procedures. Results Processing significantly reduced the anti-nutrient content and increased protein content of Ukwa flours. Up to 51.72% reduction of tannin was obtained by dehulling. Defatting, malting and dehulling resulted in 18.75, 34.37 and 65.62% reduction respectively in oxalate content. Highest reduction was obtained by dehulling, and was 70.69% in phytate, 79.95% in saponin, and 48.17% in trypsin inhibitor activity. Crude protein content of snack bars had 16.16 to 25.46% substitution main effect, and 19.43 to 22.65% processing main effect. In-vitro protein and starch digestibility increased with processing and decreased with increase in substituted level of Ukwa in the blend. Improvement, up to 9.97% by dehulling, 9.86% by malting and 8.64% by defatting, was recorded in in-vitro protein digestibility. An increase of 3.00 to 24.10% by defatting, 5.90 to 29.09% by malting and 9.70 to 31.80% by dehulling was recorded in in-vitro starch digestibility. Discussion Our study revealed that, all the processing methods adopted reduced the anti-nutrient content of ukwa flours. Protein content and total essential amino-acid (TEAA) showed significant increase with increased substituted level of ukwa flour. In-vitro protein and starch digestibility decreased with increase substituted level of ukwa flour. Snack bars formulated with 20% Ukwa showed the highest in-vitro starch and protein digestibility irrespective of the method of processing. Malted Ukwa based snack bars recorded the highest values of TEAA. Processing of this nutritious seeds and use of its flour to develop snack bars could enhance utilization and give convenience to consumers and encourage extensive farming of the crop.